2020
DOI: 10.1007/s10973-020-10025-1
|View full text |Cite
|
Sign up to set email alerts
|

Bulky-substituted phthalodinitriles and cobalt and copper phthalocyanines based on them: synthesis, thermal analysis and spectroscopic properties

Abstract: By the nucleophilic substitution of the nitro group in 4-nitrophthalononitrile for the residues of alkoxy-substituted phenols, the synthesis of alkoxyphenoxyphthalonitriles was carried out. By template condensation of the substituted phthalonitriles obtained with copper and cobalt acetates at 200 °C, the corresponding phthalocyaninates were obtained. The conditions for the isolation and purification of the complexes synthesized were selected. The stability of substituted phthalonitriles and phthalocyaninates s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…It is well known that non-covalent interactions between two or more phthalocyanine (Pcs) molecules cause their derivatives to aggregate, leading to their low solubility in the majority of solvents. 37,38 We observed that Cu-based Pcs give poor solubility and make clusters with time in chlorobenzene, a solvent used for device fabrication. Thus, the likely cause of the PV underperformance seen in some MPcs could be attributed to a lesser degree of solubility and the molecular accumulation that prevent the efficient energetic coupling and introduce recombination centers, thus responsible for the lower PCE measured for PSCs.…”
Section: Photovoltaic Performance Of Pscs With Mpcs As Htmsmentioning
confidence: 99%
“…It is well known that non-covalent interactions between two or more phthalocyanine (Pcs) molecules cause their derivatives to aggregate, leading to their low solubility in the majority of solvents. 37,38 We observed that Cu-based Pcs give poor solubility and make clusters with time in chlorobenzene, a solvent used for device fabrication. Thus, the likely cause of the PV underperformance seen in some MPcs could be attributed to a lesser degree of solubility and the molecular accumulation that prevent the efficient energetic coupling and introduce recombination centers, thus responsible for the lower PCE measured for PSCs.…”
Section: Photovoltaic Performance Of Pscs With Mpcs As Htmsmentioning
confidence: 99%
“…В этой связи разработка подходов к синтезу таких соединений является ключевым направлением химии металлофталоцианинов и перспективных материалов на их основе [96]. Металлокомплексы фталоцианинов магния, кобальта, меди и цинка получают путем сплавления соответствующего нитрила с солью металла (схема 5) [97][98][99][100][101][102][103][104][105][106][107].…”
Section: синтез и спектральные свойства феноксизамещенных металлофтал...unclassified
“…Phthalocyanine has strong absorption in the red light region and good photothermal stability, and it is a good photothermal conversion material. 26,27 The absorption band of phthalocyanine can be further red-shifted to the near-infrared region by structural modifications, which benefits its further application. 28 Manganese phthalocyanine has strong light absorption in the near-infrared region and high photothermal conversion efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon-based nanomaterials such as graphene and carbon nanotubes are the third type. Efficient photothermal materials are the ones which have strong absorption, high photothermal conversion efficiency, and good light stability. , Phthalocyanine is a kind of functional compound having a large conjugated system with 18 π electrons in plane. Phthalocyanine has strong absorption in the red light region and good photothermal stability, and it is a good photothermal conversion material. , The absorption band of phthalocyanine can be further red-shifted to the near-infrared region by structural modifications, which benefits its further application . Manganese phthalocyanine has strong light absorption in the near-infrared region and high photothermal conversion efficiency. , Due to the planar structure of phthalocyanine, it may have little negative effect on the performance of phase change material when these two are mixed together in the core of the microcapsules.…”
Section: Introductionmentioning
confidence: 99%